Anna Karakatsouli, «Μαχητές της ελευθερίας» και 1821: Η ελληνική επανάσταση στη διεθνική της διάσταση [“Freedom Fighters” and 1821: The Greek Revolution in its transnational dimension] - Tzourmana, Yanna (Historein, 2018)
Anna Karakatsouli. «Μαχητές της ελευθερίας» και 1821: Η ελληνική επανάσταση στη διεθνική της διάσταση [“Freedom Fighters” and 1821: The Greek Revolution in its transnational dimension]. Athens: Pedio, 2016. 344 pp.